Mental Health of Medical Students: A Bibliometric Analysis with Scopus Indexation - Desvita, Widea Rossi; Aristiani, Windy; Yuniasih, Dewi; Sumarno, Andhira Setya Yudha (Ahmad Dahlan Medical Journal, 2025)
Medical students are particularly susceptible to mental health challenges arising from academic pressure, clinical demands, and social expectations, which contribute to high rates of anxiety, depression, and burnout that jeopardize both well-being and professional performance; consequently, this study aimed to map the global research landscape on medical student mental health by conducting a bibliometric analysis of Scopus-indexed publications from 2013 to 2023 using a systematic search with keywords such as “medical student,” “mental health,” “depression,” “anxiety,” and “burnout,” followed by the extraction of metadata including titles, abstracts, authors, keywords, journals, and institutions, and subsequent analysis with VOS viewer software to visualize publication trends, collaboration networks, and research hotspots; the analysis of 7,126 publications revealed that “depression,” “anxiety,” and “burnout” were the most frequent keywords, identified key global collaborators, and indicated a surge in research activity during the COVID-19 pandemic, ultimately underscoring the increasing attention to mental health issues among medical students and highlighting the need for targeted interventions such as curriculum reform, enhanced mental health support programs, and resilience training to inform future research and guide policylevel strategies.